Interaction design and methodology of robot-assisted therapy for children with severe ASD and ADHD - Anara Sandygulova; Zhanel Zhexenova; Bolat Tleubayev; Aidana Nurakhmetova; Dana Zhumabekova; Ilyas Assylgali; Yerzhan Rzagaliyev; Aliya Zhakenova (Paladyn, Journal of Behavioral Robotics, 2019)
This paper presents a patient-centered interaction design of Robot-Assisted Therapy or Robot-Assisted Play (RAP) applications for children with a diverse form of Autism Spectrum Disorder (ASD) combined with Attention Deficit Hyperactivity Disorder (ADHD). Through our iterative evaluation process based on observations of fourteen children over several sessions and interviews with their parents, we continuously refined the behaviors of a humanoid robot NAO that are now ready to be used for research on Robot-Assisted Therapy. This paper also reports the design of RAP methodology that might be helpful in assimilating iterative input from stakeholders such as children, parents and therapists to customize technology for other populations with special needs.
Keywords: autism spectrum disorder (ASD); attention deficit hyperactivity disorder (ADHD); robot-assisted therapy; robot-assisted play; interaction design methodology; type of access: open access